BULLYING DI SEKOLAH - Mashar, Riana (Edukasi: Jurnal Penelitian dan Artikel Pendidikan, 2011)
Bullying is violent behavior that often occurs in schools, either verbal or physical violence. Victims of bullying will megalami many psychological disorders due to trauma, and will even be able to be perpetrators of bullying in the future.